Usaha Produksi Bibit Bawang Merah Melalui Peningkatan Ketahanan Tanaman Dari Serangan Hama Dan Infeksi Penyakit Di Desa Taman Ayu Lombok Barat - I Ketut Ngawit; Ahmad Zubaidi; Wayan Wangiyana; Ni Wayan Sri Suliartini (Fakultas Pertanian Universitas Mataram, 2020)
Due to the increasing use of inorganic fertilizers and pesticides, the prototype of the onion seed bulb known as the Ampenan Cultivar, its superiority has been declining from year to year. This phenomenon is characterized by the increasing size of the seed bulbs reaching 400-500 cloves kg-1 (while the size of normal seed tubers is 700-800 cloves kg-1), is less dense, has no breath, and grows less than 95%. Actions taken to overcome these problems are, training and direct field guidance through demonstration plots on efforts to increase the quantity and quality of onion seed tuber production by applying repeated clone selection techniques, optimal application of organic soil improvement materials and regulation of intercropping cropping patterns between shallots with peanut plants as an antidote to pest and disease infections. Based on the evaluation of all activities, the results obtained from the implementation of this program are: The target farmers attending the training and demonstration plot implementation were very enthusiastic. The appropriate technology that was introduced can be well received because it gives higher results and benefits compared to conventional businesses that have been undertaken so far. More benefits are gained by applying this integrated ecological farming model because, very little is needed for fertilizers and pesticides, weeding is easier, irrigation is efficient and farmers get additional products from peanut products. Besides being able to provide added value economically, agronomically the legume crop is very beneficial because it can protect plants from pest, weeds and diseases and restore soil fertility for sustainable farming.